2016
DOI: 10.1007/s11244-016-0626-7
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Parameters on the Microwave-Based Soot Load Determination of Diesel Particulate Filters

Abstract: Diesel Particulate Filters (DPF) are an essential part of today's diesel exhaust gas aftertreatment systems. For an effective filter regeneration strategy, the precise knowledge of the actual trapped soot mass is essential. Besides the state-of-the-art technology of determining the soot load via pressure drop and/or model-based, a microwave-based method enables direct and in situ soot load detection. Thereby, an electric field is impressed into the filter housing and the power transmission is measured, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…The test procedure is depicted in Figure 2 . In contrast to previous works on microwave-based DPF monitoring, where a constant particle concentration was present in the exhaust [ 3 , 6 ], here, different operation points (①–⑦) with a distinct soot emission rate were achieved by varying several engine parameters. This leads to different soot loading rates of the filter within the test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The test procedure is depicted in Figure 2 . In contrast to previous works on microwave-based DPF monitoring, where a constant particle concentration was present in the exhaust [ 3 , 6 ], here, different operation points (①–⑦) with a distinct soot emission rate were achieved by varying several engine parameters. This leads to different soot loading rates of the filter within the test.…”
Section: Methodsmentioning
confidence: 99%
“…This technique has been introduced by several groups and is considered very promising [ 3 , 4 , 5 ]. In our own previous studies, the microwave-based filter monitoring was tested under constant engine operation conditions [ 3 , 6 ]. Recently, Sappok et al showed that the microwave-based system is also suitable for applications under non-steady operation conditions [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A design model of microwave based regeneration system is developed as shown in figure 2. Microwave radiations produced by Vector Network Analyzers (VNA) were used by Feulner et al, for determining the soot loading in the DPF [69]. Electromagnetic filed is impressed to the filter housing which acts as resonator through one or two ports.…”
Section: ′ + ′' = (5)mentioning
confidence: 99%
“…There are already strategies to distinguish between soot and ash loading [21]. Important noise factors are soot humidity and temperature [22]. Unlike systems that are designed for TWC, where an operation in the resonance mode is envisaged, mostly transmission measurements are conducted [23].…”
Section: (3) Particulate Filtersmentioning
confidence: 99%